COST-EFFICIENT SCALING STRATEGIES FOR CLOUD-BASED TRANSACTION SYSTEMS: A TECHNICAL DEEP DIVE - Dharga Panduranga Kolla (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The cost-effective scaling techniques for cloud-based transaction systems in the contemporary digital economy are examined in this extensive technical article. The article looks at several cloud infrastructure optimization topics, such as storage tiering tactics, container orchestration, auto-scaling techniques, and vertical and horizontal scaling methodologies. It examines resource usage trends, performance indicators, and sophisticated monitoring strategies across several cloud platforms. The article also looks into applications unique to the financial services and e-commerce sectors, showing how businesses can successfully strike a balance between operational expenses and performance standards. It offers insights into attaining optimal cost effectiveness while preserving system performance and reliability in cloud environments by carefully examining caching techniques, monitoring tools, and infrastructure management.